Airway management in obese patients: The need for lean strategies. (June 2019) - Godoroja, Daniela; Sorbello, Massimiliano; Margarson, Michael
Abstract: Airway management is often the major concern of anaesthetists when presented with a morbidly obese patient for general anaesthesia. All anaesthetists are encountering increasing numbers of these patients, presenting for all types of surgery. With the particular experience gained from bariatric surgery worldwide, there is now a greater evidence base to support and guide our practice. This review article aims to provide an update of the key points in safe airway management in the obese, with a focus on pre-operative airway assessment and intra-operative airway management. Highlights: Apnoeic desaturation occurs early and progresses rapidly in the obese. Time is not on our side. Difficult facemask ventilation is common and the immediate availability of adjuncts and competent assistance is essential. The incidence of difficult laryngoscopy is similar to the non-obese but when it occurs a 'cannot intubate cannot oxygenate' scenario can rapidly develop. Surgical airway may be extremely difficult or impossible in the obese. The threshold for awake intubation should be low. Traditional markers of difficult laryngoscopy and intubation should be used, adding in that difficulty is more common in males and those with an increased neck circumference or presenting obstructive sleep apnoea.